O desafio global ante a crise financeira internacional e o fundamento da valorização do trabalho humano - Duarte, Juliana Ferreira Antunes (2009)
The job received a lot of treatments over the history of humanity, from the individual work to the collective, in the early communities, slavery, serfdom, guilds, even the proletariat work ways in a modern society, acting a directly correlation with the government ways and conducting economic order. The international economic crisis that began in 2008, and the increasing negative externalities arising from liberal capitalism unrestrained clamor for solutions, enabling delivery and satisfactory human rights in all dimensions, ensuring that all existence, which places work as an instrument. The historical analysis and cultural foundation of the recovery of human work shows there is no common unit of measure of economic value between men, which includes the society only by their individual productive force, in which everyone burns. The human work, directed the pursuit of full employment is an instrument builder of human rights in all dimensions, because the inserts in society by virtue of his work, cleansing the external economic and social effects. Therefore, the State, private entities and citizens have the challenge of ensuring every individual a job, just and dignified, whose outcome will lead to satisfactory human rights in all dimensions, according to the dictates of human capital of a fraternal company